STRATEGI KOMUNIKASI GURU BIMBINGAN KONSELING DALAM MENANGANI SISWA BERMASALAH - M, St Rosmawati; Nensilianti, Nensilianti; Juanda, Juanda (Wahana Literasi: Journal of Language, Literature, and Linguistics, 2022)
This study examines the communication strategy of counseling guidance teachers in dealing with problematic students at SMK Darussalam Makassar. Analysis of the data in this study used a functional systemic linguistic approach (LSF), namely to identify forms of communication strategies for counseling teachers in dealing with problematic students. The data of this study are in the form of clauses obtained from the results of conversations between counseling guidance teachers and problem students. The type of research used in this research is qualitative with descriptive method. The research data is in the form of writing from phrases, sentences, and clauses resulting from the conversation between the counseling teacher and the problem students. The source of the data from this study came from the recorded conversations between the counseling guidance teacher and problematic students during the counseling process. Data collection techniques, namely observation and interviews. Data analysis techniques, namely data reduction, data presentation, and verification of research results. The findings in this study are in the form of interpersonal themes based on clauses as messages, clause systems (MOOD) in the form of imperatives based on clauses as an exchange of meaning, and forms of material processes based on clauses as an exchange of meaning.